2010
DOI: 10.1136/bjo.2010.185793
|View full text |Cite
|
Sign up to set email alerts
|

Strabismus and discrimination in children: are children with strabismus invited to fewer birthday parties?

Abstract: Children aged 6 years or older with a visible squint seem to be less likely to be accepted by their peers. Because this negative attitude towards strabismus appears to emerge at approximately the age of 6 years, corrective surgery for strabismus without prospects for binocular vision should be performed before this age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 21 publications
1
40
0
1
Order By: Relevance
“…This implies that we should comprehensively consider patient self-esteem and psychosocial characteristics during treatment to obtain better satisfaction and quality of life. As Granet suggested, it is reasonable to conclude that some patients find that obtaining a normal appearance is more important due to social responses to strabismus[33], and physical characteristics should be given the same value as functional characteristics in strabismus treatment[34]. …”
Section: Discussionmentioning
confidence: 99%
“…This implies that we should comprehensively consider patient self-esteem and psychosocial characteristics during treatment to obtain better satisfaction and quality of life. As Granet suggested, it is reasonable to conclude that some patients find that obtaining a normal appearance is more important due to social responses to strabismus[33], and physical characteristics should be given the same value as functional characteristics in strabismus treatment[34]. …”
Section: Discussionmentioning
confidence: 99%
“…Similarly in young children, squint has been linked to lower psychosocial functioning, poorer interpersonal relationships and lower self-esteem [15,16]. It has been shown that children as young as 5 years are significantly more likely to have negative social reactions to peers with strabismus [13,14] and that teachers rate photographs of children with strabismus more negatively than those with straight eyes [15]. …”
Section: Introductionmentioning
confidence: 99%
“…Difficulties with self‐image, securing employment, interpersonal relationships, school, work, and sports were first documented in 1993 in the report of a case–control study of strabismus patients older than 15 years . Since that time, many experimental and observational studies have documented the psychosocial disadvantages for both children and for adults with manifest strabismus, identifying that strabismus and its non‐surgical treatments (patches or spectacles) rendered children less socially acceptable, particularly by other children aged 6 years or more . Social acceptance and inclusion are central to the concept of participation, a factor that is believed to be an important determinant of quality of life, perhaps particularly in children .…”
mentioning
confidence: 99%